A *new* program for graphic design - Reinfurt, David (Los Angeles, CA : Inventory Press ; New York, NY : D.A.P. Distributed Art Publishers, 2019)
"A *New* Program for Graphic Design is the first Communication Design text book expressly of and for the 21st century. Synthesizing the pragmatic with the experimental, A *New* Program for Graphic Design builds upon mid- to late-20th-century pedagogical models to convey advanced principles in an understandable form for students of all levels. David Reinfurt, a graphic designer, writer, and educator, has developed a design curriculum at Princeton University in which three courses provide a broad and comprehensive introduction to the field for students coming from a range of other disciplines. These courses-Typography, Gestalt, and Interface-are the foundation of this book. Through a series of in-depth historical case studies and assignments that progressively build in complexity, the book serves as a practical guide to visually understanding and shaping the increasingly networked world of information and design"--
Minimal Level Cataloging Plus.
boek